Valuing indigenous cattle breeds in Kenya: An empirical comparison of stated and revealed preference value estimates - Scarpa, R.; Ruto, E.S.K.; Kristjanson, Patricia M.; Radeny, Maren A.O.; Drucker, Adam G.; Rege, J.E.O. (Elsevier, 2003)
In this study we compare revealed and stated-preference approaches to value traits of cattle in Kenya. The premise is that much can be learnt about non-market values of indigenous animal genetic resources (AnGR) from the use of multi-attribute stated-preference methods, if these compare well with revealed-preference results. The objective is to investigate the performance of choice experiments (CEs) in Maasai cattle trading, by conducting an external test of preference consistency. We compare value estimates for cattle attributes from CEs data with those from hedonic analysis of actual transactions by the same population of traders, in the same markets and over the same period. If CEs perform well, they can be used to investigate values of those genetically-determined livestock traits currently not prominent in pastoralists’ populations, but desirable candidates for breeding or conservation programmes (e.g. disease resistance). The results indicate that CE estimates pass the external test and appear to be adequately precise in estimating values for cattle traits that are relevant in market transactions for Maasai traders. Accounting for taste and variance heterogeneity does not change this conclusion. CEs may, therefore, be a promising tool for valuing phenotypic traits expressed by indigenous AnGR.